Exploring novel furochochicine derivatives as promising JAK2 inhibitors in HeLa cells: Integrating docking, QSAR-ML, MD simulations, and experiments - Duangjai Todsaporn; Kamonpan Sanachai; Chanat Aonbangkhen; Athina Geronikaki; Victor Kartsev; Boris Lichitsky; Andrey Komogortsev; Phornphimon Maitarad; Thanyada Rungrotmongkol (Computational and Structural Biotechnology Journal)
Cervical cancer, largely driven by high-risk human papillomavirus (HPV), remains a global health challenge. Janus tyrosine kinase 2 (JAK2) has emerged as a promising therapeutic target for HPV-induced malignancies. This study employed both in silico and in vitro approaches to discover novel JAK2 inhibitors from a library of 76 furochochicine (FCC) derivatives. Twenty-nine compounds were selected via virtual screening, synthesized, and tested for cytotoxicity against HeLa cells. Four FCCs showed potent cytotoxicity with selectivity indices (SI) greater than 3. These cytotoxicity data were used to construct QSAR models with machine learning; eXtreme Gradient Boosting (XGB) yielded the best performance (RMSE = 0.177, R² = 0.831, MAPE = 2.93 %) and was used to predict additional FCC derivatives. FCC90 emerged as a lead compound with strong predictive accuracy (MAPE = 1.43 %) and selectivity (SI = 3.25). JAK2 kinase assays revealed strong inhibition by FCC6, FCC27, and FCC90 (IC₅₀ = 9.10–27.34 nM), with FCC6 and FCC27 surpassing ruxolitinib. Flow cytometry confirmed apoptosis and sub-G1 cell cycle arrest. Molecular dynamics simulations supported the stability of FCC–JAK2 complexes. Furthermore, all active compounds met extended Rule of Five (eRo5) criteria. These findings highlight the potential of FCC derivatives as JAK2 inhibitors for cervical cancer therapy.